Woman and the Conservation of Nature in Erin Brockovich Film - Fitri Yuniar Santoso (LITERA KULTURA : Journal of Literary and Cultural Studies, 2022)
This study analyzed the environmental movement to preserve the nature by an ecofeminist in a movie entitled Erin Brockovich directed by Steven Soderbergh (2000). The study focused on the main character of the film, who represented herself as an ecofeminist. This study used the theory of ecofeminism by Vandana Shiva (1998) and mixed it with the cinematography theory by Heiderich. Moreover, this study also accomodated the power relation theory by Foucault as the supporting theory. Identifying the connectedness between woman and nature shown by Erin Brockovich’s actions in the film is the purpose of this study. The research revealed the impacts of natural conservation carried out by Erin Brockovich due to her response to natural destruction, which is triggered by a relation of power among institutions, government, and agencies that are represented by male domination. The research utilized Shiva’s arguments on the relationship of those elements in the movie. The sources of the study were taken from the film and the script of the film. The result of this study provided a conclusion that nature is in great suffer due to the exploitation, destruction, vandalism which were done by government, institutions, and some agencies. They are considered to be patriarchy chain reaction. Keywords: ecofeminism, destruction, conservation, power relation.